Fifty key British films - Barrow, Sarah; White, John, 1956- (Routledge key guides., 2008)
In Fifty Key British Films, Britain's best known films such as Clockwork Orange, The Full Monty and Goldfinger are scrutinised for their outstanding ability to articulate the issues of the time. This is essential reading for anyone interested in quality, cult film.